Effects of an educational Campaign about beans on a group of women. - Dumani, Marcela (2004)
The effects of an educational Campaignabout beans on a group of middle-class mothers with schoolchildren who were the target group of this study, arepresented in this article. The particular characteristic of thisgroup of women was that their children had also beenexposed to the Campaign. The students were the “interactivegroup”, because their close contact with their mothers,allowed them to act as a communication channel to reinforcethe messages addressed to them. The effects are evaluated asknowledge, attitudes, and practices of the mothers withregards to beans, comparing findings with “successindicators” proposed for the Campaign. With the dataobtained in the initial assessment it was also possible to makequantitative comparisons of some of the practices. Resultsrevealed that the Campaign had positive effects on women.An important increase in bean consumption by families, apositive attitude about beans, and improvements in theirpreparation, consumption, and preservation were observedafter the Campaign.